RELEVANSI KONSEP PENDIDIKAN MUHAMMAD BASIAUNI IMRAN DENGAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH - Mauludea, Hana; Nurhadianto, Nurhadianto; Sahrandi, Sahrandi (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2023)
Muhammad Basiuni Imran's educational concept is an educational concept that cannot be separated from the humanist process. The process is to become human, to reach the level of humanity through character building. History lessons have the potential to convey moral messages that can help shape student character. This study discusses the importance of the pedagogical concept of Muhammad Basiuni Imran for personality development in history lessons. This research uses qualitative methods and literature searches to explore various sources related to this research. This study aims to find the pedagogical concept of Muhammad Basiuni Imran with personality development in history lessons. The substantive content of the story includes various moral values that can be adopted and instilled in students, so that the process is a process of humanizing the younger generation and the process of forming character, achieving human dignity.Â Keywords: Education Concept, Muhammad Basiuni Imran, Character Education, Historical Education.Â Â